DETEKSI DAERAH TERCEMAR LUMPUR ASAM MENGGUNAKAN DATA LANDSAT 7 ETM BERDASARKAN SUHU PERMUKAAN TANAH - Sulma, Sayidah; Pasaribu, Junita Monika; Haryani, Nanik Suryo (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2014)
The high human activity in the mining and industrial areas increases the potency for hazardous and toxic waste pollution. One form of hazardous and toxic waste is acid sludge, a mixture of hydrocarbons and sulfuric acid derived from the disposal of plant wax. This study aims to detect and monitor the acid sludge contaminated area based on the Land Surface Temperature (LST) derived from Landsat 7 ETM multi-temporal data. The steps included data collection, development of LST algorithms for Landsat 7 ETM resulted from regression of Terra-MODIS LSTand Tb of Landsat data, calculation of LST using Landsat 7 ETM multi temporal data and monitoring LST in polluted areas. The distribution of the MODIS LST value can be used as a reference in determining the LST from Landsat 7 ETM by performing linear regression models with a coefficient determination of 0.84. Based on the analysis of LST, the contaminated areas have a higher temperature compare to the uncontaminated area. There is no significant relationship pattern to the land and land recovery process. This may indicate that the recovery process in that area did not significantly affect the temperature.